IMPLEMENTASI KREATIVITAS SISWA/I DALAM EDUKASI PENGETAHUAN DASAR PRO-AKTIF ANAK IMIGRAN INDONESIA DI MALAYSIA - Maulana, Yoga Arif; Dewi, Berliana Rosita; Sadubi, Sultan Reynard; Amellia, Nazwa; Sidik, Aaliyah Maharani Putri; Andani, Alifia Aulia; Madihah, Maysa; Agusman, Desi Destiana; Azizah, Siti Nur (Jurnal Pengabdian Kolaborasi dan Inovasi IPTEKS, 2025)
The decline in the interest of Indonesian students in learning can threaten the quality of education and human resources that have an important role in the future of the nation. Basic knowledge about civic and cultural education, which should be an important understanding for students, is not in line with expectations, especially for Indonesian students who are abroad. This is exacerbated by the negative effects of unsupervised use of gadgets, which makes students more interested in outside cultures and reluctant to learn about local cultures. In addition, the lack of competence of educators and unattractive learning methods also contribute to the low enthusiasm of students. To overcome this problem, we carry out a learning program by involving students' creativity in proactive basic knowledge education for Indonesian immigrant children at At-Tanzil Fostered School, Malaysia. This program involves 20 Kindergarten students and 7 students in grades 1-2 of Elementary School, and will be held on October 2, 2024 with the Youth.id Team. This program uses a learning approach that provides a space for creativity for students to actively participate in learning, which includes hygiene materials, mathematics, and cultural introduction. This approach is expected to increase students' interest in learning and contribute to the development of more effective and inclusive educational methods.